Health care services satisfaction and associated factors among people living with HIV/AIDS at Kibuye referral hospital, Rwanda - Abdou, Nizeyimana; Habtu, Michael; Marete, Onesmus; Mochama, Monica; Rutayisire, Erigene; Dida, Gabriel O. (International Journal Of Community Medicine And Public Health, 2021)
Background: Patient satisfaction surveys have gained great attention as meaningful parameters for evaluating quality improvement in healthcare organizations. At Kibuye referral hospital, healthcare utilization and health care services for people living with HIV/AIDS (PLWHA) has been low, as attested by poor adherence to medication and weakening of patients due the disease progression. The main objective of this study was to assess healthcare services satisfaction and associated factors among people living with HIV/AIDS Kibuye referral hospital, Rwanda. Methods: An institutional-based cross-sectional design was used to select 277 study participants who were interviewed by use of a structured questionnaire, and the data analyzed quantitatively. Two focus group discussions were performed, after which the interviews were transcribed in verbatim and analyzed thematically. Results: The overall level of PLWHA satisfaction was 95.0%. In multivariate analysis, social class and age were found to be the main predictors of PLWHA satisfaction (AOR=10.218, 95% CI=1.39, 74.88, p=0.002) and (AOR=0.39, CI=0.121 to 1.186, p=0.005), respectively. Qualitative study outcome showed that health care service delivery at Kibuye referral hospital is measured by a number of factors, including timeliness of health care service delivery, meeting needs of clients and paying attention in provision of health care services. Conclusions: The level of patient satisfaction was found to be high. When individual was of high-class status in the society, and were above 20 years of age, his or her satisfaction increased. The study recommends that PLWAs are treated equally so as to improve service delivery, particularly among people living HIV/AIDS.